2011
DOI: 10.1007/s10164-011-0306-9
|View full text |Cite
|
Sign up to set email alerts
|

What exactly is ‘local song’ in a population of ortolan buntings with a common dialect?

Abstract: Previous studies have shown that ortolan buntings (Emberiza hortulana) exhibit apparent dialect variation. Neighbouring males typically share the same final phrase of a simple two-part song. Consequently, the final phrase was considered to be the dialect cue important for discriminating between males from a local population and strangers. Recently, it was shown that in an isolated and fragmented population of the ortolan buntings in Norway there was no local dialect in the above-mentioned sense. Norwegian male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Thus, some other hypothesis is necessary to explain the delayed song learning that promotes dialect development in this species. Our results also raise important questions about why male dickcissels respond equally aggressively to local and to foreign dialects while territorial males in so many other species (Bradley et al, 2013;McGregor, 1983;Osiejuk et al, 2012) respond more aggressively to local song than to foreign song.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, some other hypothesis is necessary to explain the delayed song learning that promotes dialect development in this species. Our results also raise important questions about why male dickcissels respond equally aggressively to local and to foreign dialects while territorial males in so many other species (Bradley et al, 2013;McGregor, 1983;Osiejuk et al, 2012) respond more aggressively to local song than to foreign song.…”
Section: Discussionmentioning
confidence: 81%
“…If this is the case, territorial individuals should respond more aggressively to a foreign dialect than a local dialect. However, this prediction is not typically met in playback studies (Lemon, ; Osiejuk, Bielecka, & Skierczynski, ; Podos, ), and so, the deceptive mimicry mechanism is unlikely. However, a small number of studies present evidence that could be interpreted as support for the predictions of deceptive mimicry (Baker, Thompson, Sherman, & Cunningham, ; Balaban, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, twenty years of research on a continuous and abundant population from Western Poland has revealed no age‐related changes in repertoire size, contents or overall song diversity (e.g. Skierczyński & Osiejuk, ; Osiejuk, Bielecka & Skierczyński, ; Jakubowska & Osiejuk, ; own unpubl. data).…”
Section: Discussionmentioning
confidence: 99%
“…Both the initial and final local phrases of experimentally manipulated songs increase the responsiveness of males more than full foreign song (Osiejuk et al. ). One possible hint for explaining this phenomenon comes from syrinx morphology and biomechanics.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that despite its within-population homogeneity, the final song phrase is not the only signal of 'locality'. Both the initial and final local phrases of experimentally manipulated songs increase the responsiveness of males more than full foreign song (Osiejuk et al 2012). One possible hint for explaining this phenomenon comes from syrinx morphology and biomechanics.…”
Section: Discussionmentioning
confidence: 99%